Peningkatan keterampilan pemecahan masalah interpretasi data melalui model pembelajaran kooperatif tipe TAI peserta didik kelas v sekolah dasar - Sakti, Rino Aldyan; Sularmi, Sularmi; Surya, Anesa (Didaktika Dwija Indria, 2019)
The purpose of the research is to improve problem solving the skills of data interpretation through the use of the team assisted individualization type cooperative learning  model in fifth grade students of SD N Kemasan 2 No. 248 Surakarta 2018/2019 school year. Classroom Action Research (CAR) is conducted in 3 cycles, each cycle consisting of 2 meetings with 4 stages, namely planning, action, observation, and reflection. The subjects of this study were teachers and 5th grade students, amounting to 28 students. This study uses observational techniques, interviews, documentation, and tests. Data analysis using interactive data analysis with steps of data reduction, data presentation, and conclusions. The data validity test technique uses source triangulation and technical triangulation. The results showed that the average score of pre-action class with 14.% classical completeness increased to 43% classical completeness in the 1st cycle,  increased with a classical completeness of 60.71% in cycle II. and increased again with a classical completeness of 89.29% in cycle III. Based on the results of the study, it can be concluded that through the application of the team assisted individualization type cooperative learning  model can improve the problem solving the skills of data interpretation in class V SD N Kemasan 2 No. 248 Surakarta 2018/2019 school year.